COMPARISON OF EPINEPHRINE AND PHENYLEPHRINE CONCENTRATIONS FOR USE DURING INTRANASAL PROCEDURES - Yoshikawa, Mamoru; Syouji, Kazuhiro; Ota, Shuji; Tanifuji, Yasumasa (JIBI INKOKA TEMBO, 2006)
During intranasal procedures such as nasal intubation, epinephrine is generally used to prevent bleeding. However, few studies have reported on the effective concentrations of vasoconstrictors administered into the nasal cavity. The present study compared the optimal doses of epinephrine and phenylephrine for the prevention of bleeding during intranasal procedures. The subjects were 9 healthy adult volunteers (5 men, 4 women) with a mean age of 26.3 ± 3 years (range, 24-32 years), no past history of nasal or paranasal cavity diseases, and no history of upper respiratory inflammation within a week prior to the study. Two ml of each of 0.02-0.001% epinephrine, 0.5% or 0.1% phenylephrine hydrochloride or physiological saline was soaked in gauze and placed in the right nasal cavity for 3 min. Before and after the drug application, the mucosal color and vasoconstriction was assessed by endoscopy, and an airflow (pressure and flow curves) was measured with an airflow meter. Endoscopy performed to assess the mucosal color and vasoconstriction revealed that except with physiological saline, mucosal contraction and anemia-like whitening of the mucosa of the inferior nasal concha were seen with all of the drug solutions employed. As compared to that observed for physiological saline, airflow improved significantly with 0.02% or 0.01% epinephrine, or 0.5% phenylephrine. The optimal doses of epinephrine and phenylephrine for the prevention of bleeding during nasal intubation thus appear to be 0.01% and 0.5%, respectively.